Public practice, knowledge and attitude on managing kitchen and food wastes in Bintulu, Sarawak, Malaysia - Che Hamzah, Nurul Husna; Sanusi, Azira; Khairuddin, Nozieana; Azman, Nor Shafinaz; Lahuri, Azizul Hakim (EJournal Publishing, 2022)
Kitchen and food wastes discarded from the food related premises contributes to the high proportion of organic waste that end up in its landfill. The methane gas released during the dumping of food waste at the landfills is unsafe because the gas is flammable, and it is also a strong greenhouse gas. To tackle this problem, efforts are necessary to reduce the kitchen waste generated and to manage the disposal of waste sustainably. However, for this initiative to be successful, the owners and workers in food sector play an important role. The main objective of this study was to evaluate the practice, knowledge, and attitude of the food premises owners towards managing the kitchen and food waste in the district of Bintulu, Sarawak. Thus, a survey was conducted among 130 owners of randomly selected food premises. The collected data showed that food waste has the largest portion (46.7%) produced in Bintulu compared to other MSW such as plastic, paper, glass, metal, etc. Most respondents prefer to dump the food and kitchen wastes into garbage bins (79.2%) rather than composting (6.2%), donate, reuse, and recycle. This result proved the importance of building a biogas plant for kitchen and food waste since the respondents preferred to throw away the leftover food rather than composting the food. It will also help to propose appropriate treatment technologies to support the National Solid Waste Management (SWM) Policy and National Green Technology Policy for waste-to-wealth projects.